Ensino de botânica: a importância do ensino por investigação como estratégia para alfabetização científica - Conceição, Alexandre Rodrigues da (2020)
This research aims to verify the contribution of Science Education through research as a didactic strategy capable of promoting Scientific Literacy. The chosen theme was Botany, which presents several weaknesses in the teaching and learning process. In this sense, we seek to answer the central question of this research: How can Teaching by Research contribute to learning the contents of Botany in the early years of Elementary School? In this sense, we developed an Investigative Teaching Sequence (SEI) to work on the structures of plants and the birth of bananas with students from the 2nd year of Elementary School. We justify the choice of this school level as being a proposal of the National Common Curricular Base (BNCC). This study has a qualitative approach, of a descriptive and explanatory nature. This research was carried out on the 7th and 27th of August 2019 with the research location of the Municipal School Professor Noêmia Bastos in the interior of Alagoas. The collection instruments used were audio recording, graphic and textual records produced by students. For the analysis of the data we tried to establish, when possible, a relationship between some indicators of scientific literacy of the authors Sasseron and Carvalho (2008) and also of the categories proposed by Samarapungavan, Mantzicopoulos, Patrick (2008) and Howitt, Lewis; Upson (2011). The results demonstrate that teaching by research is able to contribute to the development of scientific literacy, making the classroom an environment based on argumentation, hypothesis raising and changing the teaching and student posture.